A bird in the hand is worth two in the bush: Technology search strategies and competition due to import penetration - Morandi Stagni, Raffaele; Fosfuri, Andrea; Santaló, Juan (Strategic Management Journal, 2021)
Abstract Research Summary Do firms respond to tougher competition by searching for completely new technological solutions (exploration), or do they work to defend their position by improving current technologies (exploitation)? Considering the different times to fruition for exploration versus exploitation, in the presence of heightened competition, we argue that firms might not be able to wait for the benefits of technological exploration to materialize. With a panel data set of U.S. manufacturing firms, we show that tougher competition, due to import penetration, leads to a decrease in technological exploration and an increase in technological exploitation. These effects are heterogeneous across industries, firms, and time. To obtain exogenous variation in competition we rely on both instrumental variable regressions and a difference‐in‐differences design exploiting large changes in import tariffs. Managerial Summary A firm's R&D strategy is one of the fundamental determinants of success or failure when responding to competitive threats. In this study, we examine how firms change the knowledge sources used in their R&D efforts in response to substantial increases in import penetration in their domestic market. We find that in the years that immediately follow an increase in import penetration, firms tend to rely more on familiar knowledge in the development of innovations and less on knowledge sources that were not previously used. This switch in R&D strategy also appears to be temporary (reversed in later years), and it is positively associated with an increased likelihood of survival.